(untitled) (International Journal of Creative Future and Heritage (TENIAT), 2025)
ABSTRACT This article explores the character of Seri Rama in Hikayat Maharaja Wana, the main text in the traditional Wayang Kulit Siam (also known as Wayang Kulit Kelantan) performance. Although often regarded as a form of entertainment, Wayang kulit Siam is rich in philosophy, symbolism, and educational values. Previous studies have primarily focused on visual elements and external symbolism of puppet characters, with limited attention given to the aesthetic image and moral values of Seri Rama from an Islamic perspective. This study aims to address this gap by analysing the aesthetic representation and moral dimensions of Seri Rama through the perspective of Islamic aesthetic theory. Employing a qualitative case study approach, the research involves textual analysis of Hikayat Maharaja Wana, performance observation, and descriptive thematic analysis. Findings reveal that Seri Rama embodies not only outward beauty, but also deeper values of balance, harmony and spirituality aligned with the Islamic principle of beauty. ABSTRAK Artikel ini meneliti watak Seri Rama dalam Hikayat Maharaja Wana, teks utama dalam persembahan Wayang Kulit Siam atau Wayang Kulit Kelantan. Walaupun sering dianggap sebagai hiburan tradisional, Wayang Kulit Siam sarat dengan unsur falsafah, simbolik dan nilai pendidikan. Namun, kajian terdahulu lebih tertumpu kepada aspek visual dan perlambangan luaran, dengan kurang perhatian kepada citra estetika dan nilai moral watak dari perspektif Islam. Justeru, kajian ini bertujuan menganalisis citra estetika dan nilai moral watak Seri Rama berdasarkan kerangka estetika Islam. Kajian ini mengunakan pendekatan kualitatif melalui analisis teks Hikayat Maharaja Wana, pemerhatian persembahan dan analisis deskriptif tematik. Hasil kajian menunjukkan bahawa watak Seri Rama bukan sahaja mewakili keindahan lahiriah, tetapi juga mencerminkan nilai keseimbangan, keharmonian dan spiritualiti, selari dengan prinsip keindahan dalam Islam.